1987
DOI: 10.1136/jnnp.50.11.1539
|View full text |Cite
|
Sign up to set email alerts
|

Protracted vomiting as the presenting sign of posterior fossa mass lesions.

Abstract: SUMMARY Four patients with mass lesions of the posterior fossa experienced protracted vomiting as their only symptom for extended periods of time. The responsible lesions were a cerebellar tumour in two patients, a ventricular cysticercus in one patient, and a giant vertebral artery aneurysm in another. All four cases had compression or displacement of the floor of the fourth ventricle, where the "vomiting centre" has been located. occurring in the early morning, frequently related to postural changes, and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Grossmann et al [7] described a patient with cavernoma in the medulla to the upper cervical cord detected by MRI. Torrealba et al [8] reported 4 cases of mass lesions in the posterior fossa. Patients with ependymomas of the fourth ventricle also vomit periodically [13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grossmann et al [7] described a patient with cavernoma in the medulla to the upper cervical cord detected by MRI. Torrealba et al [8] reported 4 cases of mass lesions in the posterior fossa. Patients with ependymomas of the fourth ventricle also vomit periodically [13] .…”
Section: Discussionmentioning
confidence: 99%
“…When accompanied by vertigo or raised intracranial pressure, brain diseases often cause nausea and vomiting. However, isolated central vomiting is rare [4][5][6][7][8] . We Dear Sir, Recent experimental studies have indicated a 'vomiting pattern generator' (formerly called the 'vomiting center') situated in the dorsal portion of the lateral reticular formation of the medulla, which mostly corresponds to the dorsal vagal complex (DVC) [1] .…”
mentioning
confidence: 99%